Natural phytochemicals as P2X7 receptor inhibitors for the treatment of inflammation-related diseases - Niu, Qian; Li, Jin-cai; Zhang, Meng; Zhou, Peng (Italian Journal of Food Science, 2023)
P2X7 receptor (P2X7R) inhibition is critical for reducing the overactivation of its downstream signaling pathway in autoimmune diseases. Phytochemicals are a source of medicinal compounds for various diseases and contribute to the development of effective and safe P2X7R-targeted drugs. This review is aimed at identifying and screening novel safe, effective, and economically feasible inhibitors of P2X7R from phytochemicals extracted from food and plants. The results of the docking study revealed that the VINA scores of dihydrotanshinone, baicalin, berberine, genistin, dioscin, resveratrol, apigenin, cannabidiol, esculin, and luteolin were lower than or equal to that of A740003 (P2X7R inhibitor). The VINA scores of dihydrotanshinone and baicalin were lower than or equal to JNJ47965567 (P2X7R inhibitor). Dihydrotanshinone and baicalin can be used as lead compounds for P2X7R inhibition. These active ingredients will contribute to the discovery of lead compounds and the development of innovative P2X7R agents for the treatment of autoimmune diseases.